Statement : Spain
015a_0008_001 SPAIN The National Executive Committee of the Labour Party, having heard the Report of the Leader and Deputy Leader of the Opposition, who visited London, and through them the reply of Mr. Chamberlain, together with further documented information that has been placed before it, emphatically declares its conviction that the Fascist Powers have broken their pledges and endorses the demand made by our Leaders that the investigation of the alleged breaches of the Spanish Non-Intervention Agreement should be pressed forward with the utmost speed. It demands that the Report of this investigation should be made public, and, in the event of it being found that the Agreement has either been ineffective, owing to the lack of machinery of supervision or has been definitely violated, the French and British Governments being responsible for the initiation of the Non-Intervention policy should take steps forthwith to restore to the Spanish Government their right to purchase the arms necessary to maintain the authority of the Constitutional Government in Spain and to re-establish Law and Order in her territory. To this end it urges the fullest collaboration between these Powers and other Powers who have been loyal to the Agreement. In view of the fact that the conduct of all action arising out of the Spanish situation has been entrusted to the National Council of Labour in consultation with the International Federation of Trades Unions and the Labour and Socialist International, the National Executive Committee will immediately take steps to arrange a meeting of the National Council of Labour with the object of carrying out the policy embodied in this statement. 292/946/15a/8